Shooting Accuracy in Junior High School Football Extracurricular Activities: Study Examines How Leg Muscle Power and Ankle Coordination Relate - Wahid Bintang Pangestu; Ardika Hiskia Marpaung; Dewi Maya Sary (IGI Active Living and Health Insight, 2026)
Purpose of the study: Shooting accuracy is a fundamental skill in football that significantly influences match outcomes. The relationship between biomechanical factors such as leg muscle power and ankle coordination with shooting precision remains understudied in adolescent populations. Purpose of the study: This research aimed to investigate the correlation between leg muscle power, ankle coordination, and shooting accuracy among junior high school football players participating in extracurricular activities. Materials and methods: Twenty-four male students (age 13.2 ± 0.8 years) from SMP Negeri 4 Lubuk Pakam participated in this cross-sectional study. Leg muscle power was assessed using vertical jump test, ankle coordination through single-leg balance test, and shooting accuracy via standardized target shooting protocol. Data were analyzed using Pearson correlation and multiple regression analysis in SPSS v27. Results: Significant positive correlations were found between leg muscle power and shooting accuracy (r = 0.742, p < 0.001) and ankle coordination and shooting accuracy (r = 0.681, p < 0.001). Combined variables explained 67.3% of shooting accuracy variance (R² = 0.673, p < 0.001). Conclusions: Leg muscle power and ankle coordination are significant predictors of shooting accuracy in junior high school football players. Training programs should emphasize both power development and proprioceptive exercises to enhance shooting performance.